Re-imagining education in Haiti through a lens of de-coloniality - Rudolph Damas (Quality Education for All)
Purpose – Scholars such as Hebblethwaite (2012) argue that societal elements like the pressure for students to learn French in Haiti are deeply rooted in colonial traditions which were originally intended to hinder long-term development and continue to do so within the country. The purpose of this paper is to widen the scope of Hebblethwaite’s discussion on language and question other social norms within educational institutions, which are having a negative impact on educational attainment. This purpose is accomplished by way of an empirical study of primary school education reform efforts in Haiti through a lens of de-coloniality as defined by Walter Mignolo (2005). Design/methodology/approach – Given that this is an empirical study on education reform in Haiti, I have conducted this study solely through the analysis of literature and evidence from past work on education reform in Haiti and other countries with similar challenges. The body of the research is separated into two parts, and the first is a critical historical analysis of the context. The second is a comparative analysis of two different case studies on education reform projects that have occurred in Haiti. This will also be followed by a conclusive analysis of similar efforts in communities around the world. Findings – This study demonstrates that primary school students, teachers and their communities in Haiti respond better to education development projects that place mother-tongue learning, grassroots community participation and culturally relevant pedagogy at the forefront of daily operational planning. These factors would play a key role in setting the foundation for students to be both productive Haitian citizens first and global citizens second. The literature reviewed also demonstrates that historically, education has focused far too heavily on models that work for or originate from the global north and not enough on building an education system tailored to Haiti. Research limitations/implications – Since barriers such as societal norms need to be addressed through organic grassroots movements, which take time to be effective, reform from this perspective is better suited for the longer term than the shorter term. In the conclusion, this is considered to be a limitation when it comes to identifying short-term solutions to education, especially given that grassroots projects such as Buiga-Sunrise take time to establish winning practices that support self-sufficiency. Originality/value – Literacy rates in Haiti for the year 2012 were around 48% for adults and 72% for youth (UNESCO Institute for Statistics, 2012). Not to mention that only 50% of children attend primary schools and 20% attend secondary schools (UNICEF Haiti, 2011, as cited in Jean-Marie and Sider, 2014). Such low educational attainment shows a need for greater access to education, and as much as the privatisation of schools is a significant barrier, as argued by Sider and Jean Marie, there are other impactful factors that remain to be addressed.